Synthesis of zwitterionic, hydrophobic, and amphiphilic polymers via RAFT polymerization induced self-assembly (PISA) in acetic acid. Issue 39 (22nd September 2016) - Das, Debobrato; Gerboth, Devin; Postma, Almar; Srinivasan, Selvi; Kern, Hanna; Chen, Jasmin; Ratner, Daniel M.; Stayton, Patrick S.; Convertine, Anthony J.
Abstract : Hydrophilic, hydrophobic, and combinations of these monomers were directly (co)polymerized via RAFT polymerization induced self-assembly (PISA) in acetic acid. Abstract : Polymerization induced self-assembly (PISA) in acetic acid was employed to polymerize the hydrophilic sulfobetaine monomer 2-( N -3-sulfopropyl- N, N -dimethyl ammonium)ethyl methacrylate (DMAPS) and the hydrophobic monomer lauryl methacrylate (LMA). Polymerizations were conducted from a macro chain transfer agent (macro-CTA) consisting of 66% 2-hydroxyethyl methacrylate (HEMA) and 33% poly(ethylene glycol) methyl ether methacrylate FW ∼ 300 Da (O300). A degree of polymerization (DP) of 50 was targeted for the macro-CTA in order to yield diblock copolymers with significantly larger 2 nd blocks. From the poly(HEMA- co -O300) macro-CTA, diblock copolymers of poly[(HEMA- co -O300)- b -(DMAPS)] and poly[(HEMA- co -O300)- b -(LMA)] were grown via PISA in acetic acid. In order to maintain colloidal stability, it was necessary to conduct PISA of DMAPS at 10 wt% monomer, while LMA polymerizations maintained stability at 20 wt% monomer. M n vs. conversion plots for both DMAPS and LMA show linear increases in molecular weight over the course of the polymerizations. Analysis of the molecular weight distributions revealed a progressive narrowing throughout the polymerization from an initial bimodal state. Copolymers of DMAPS and LMA were also synthesized over a large range of comonomer feed ratios. These materials show composition-dependent sizes in buffered solutions between 11 nm for the copolymer containing 80% by mol DMAPS to 75 nm for the copolymer containing 40 mol% DMAPS. PISA in acetic acid was then used to prepare copolymers of DMAPS with a range of hydrophobic polymerizable prodrug monomers as well as a polymerizable peptide macromonomer. The resultant copolymers had narrow molecular weight distributions and were readily soluble in saline solutions.